PENGEMBANGAN WAKAF TUNAI BERBASIS UMRAH DI PONDOK PESANTREN TA’MIRUL ISLAM SURAKARTA - Qi Mangku Bahjatulloh (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
The aim of this study was to determine the cash of waqf development umrah and suitability based on sharia-based cash waqf umrah in Ta’mirul Islamic boarding school. This study is a field research with qualitative methods. The object of this study is the agency of Hajj and Umrah Al Mabrur Islamic Boarding School of Ta’mirul Islam Surakarta. The method of analysis was comparation analysis, to re-examine its suitability with aspects of comparison that is pillars, of waqf terms, and conditions MUI. As well as using SWOT analysis to determine the factors that needs to be strategic. Based on the findings in this study, it can be concluded that the cash of waqf Umrah is a charity-based effort to serve the pilgrims in the Hajj pilgrimage and of waqf as well as cash. This effort combines “tijari” contract models and “tabarru” contract models, in which convey with sharia.